Character Building Of StudentsIn The Boarding School System (International Journal of Scientific Research and Management (IJSRM), 2024)
The rapid development of the times marked by advances in science and technology, whether we realize it or not, it has a sharp impact on society, including adolescents and school-age children. The positive impact arising from the development of science and technology is a great hope for all levels of society. On the other hand, the emergence of negative impacts is undeniable and has recently occurred in society, including in the world of education. Cases of bullying, student fights, skipping school, actions of against the teachers, are increasingly common. This makes parents, practitioners, organizers and observers of education quite concerned and stimulated to create and emphasize education that is able to produce students who have strong character, have akhlaqul karimah. Realizing this condition is also the responsibility of the government, the government stipulates the importance of character education in educational institutions as stated in Presidential Regulation No. 78 of 2017 concerning Strengthening Character Education. One of the efforts taken by education providers is to organize education with boarding services, namely educational services by requiring students to live in school dormitories, with the aim that the education process can run twenty-four hours, with full attention and monitoring and guidance from the boarding supervisor. With this boarding system, the school will be easier to condition students to participate in activities organized by the school, including religious education as the core of character education in theory and practice directly with the guidance of teachers in the dormitory. Boarding system education also isolates students from socializing in the wider environment which has recently been exposed to many negative influences from the internet, social media and so on. In boarding schools, students are taught to have a strong character through a maximum educational process.